Economic Evaluation of Interventions for Prevention of Hospital Acquired Infections: A Systematic Review. - Habibollah Arefian; Monique Vogel; Anja Kwetkat; Michael Hartmann (PLoS ONE)
Objective This systematic review sought to assess the costs and benefits of interventions preventing hospital-acquired infections and to evaluate methodological and reporting quality. Methods We systematically searched Medline via PubMed and the National Health Service Economic Evaluation Database from 2009 to 2014. We included quasi-experimental and randomized trails published in English or German evaluating the economic impact of interventions preventing the four most frequent hospital-acquired infections (urinary tract infections, surgical wound infections, pneumonia, and primary bloodstream infections). Characteristics and results of the included articles were extracted using a standardized data collection form. Study and reporting quality were evaluated using SIGN and CHEERS checklists. All costs were adjusted to 2013 US$. Savings-to-cost ratios and difference values with interquartile ranges (IQRs) per month were calculated, and the effects of study characteristics on the cost-benefit results were analyzed. Results Our search returned 2067 articles, of which 27 met the inclusion criteria. The median savings-to-cost ratio across all studies reporting both costs and savings values was US $7.0 (IQR 4.2-30.9), and the median net global saving was US $13,179 (IQR 5,106-65,850) per month. The studies' reporting quality was low. Only 14 articles reported more than half of CHEERS items appropriately. Similarly, an assessment of methodological quality found that only four studies (14.8%) were considered high quality. Conclusions Prevention programs for hospital acquired infections have very positive cost-benefit ratios. Improved reporting quality in health economics publications is required.